2019
DOI: 10.13102/sociobiology.v66i2.3431
|View full text |Cite
|
Sign up to set email alerts
|

Post-embryonic Development of the Seminal Vesicle in the Stingless Bee Melipona quadrifasciata Lepeletier, 1836 (Apidae: Meliponini)

Abstract: The male accessory glands of stingless bees (Apidae: Meliponini) are absent and the morphology of their seminal vesicle indicate probable secretory function by this organ. This study investigated the post-embryonic development of the seminal vesicles in males of the stingless bee Melipona quadrifasciata by histology and histochemistry. White-eyed pupae, pink-eyed pupae, brown-eyed pupae, black-eyed pupae, newly emerged and sexually mature males were studied. Seminal vesicle has a wall with a single layered epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…It has been found that the spermatozoa were continuously produced even during the mating state, and the newly eclosed males store the spermatozoa in the lumen of the vas deferens [ 25 ]. In the pupal stage of stingless bees (Apidae: Meliponini), the male accessory glands are absent and the secretory function of this organ is performed by their seminal vesicle, whereas in the adult males, the accessory glands also store the spermatozoa [ 26 ].In the current study, the development of the accessory gland and ejaculatory duct in prediapause males was poor compare to prereproductivemales. It can be argued that the delay in reproductive development may result in the absence of hormonal productionduring the diapause period, which needs to be explored in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the spermatozoa were continuously produced even during the mating state, and the newly eclosed males store the spermatozoa in the lumen of the vas deferens [ 25 ]. In the pupal stage of stingless bees (Apidae: Meliponini), the male accessory glands are absent and the secretory function of this organ is performed by their seminal vesicle, whereas in the adult males, the accessory glands also store the spermatozoa [ 26 ].In the current study, the development of the accessory gland and ejaculatory duct in prediapause males was poor compare to prereproductivemales. It can be argued that the delay in reproductive development may result in the absence of hormonal productionduring the diapause period, which needs to be explored in future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In the Neotropics there are more than 400 species into 32 genera (Camargo, 2013), which performing fundamental ecosystem services as pollinators (Michener, 2007;Freitas et al, 2009) pollinating 40-90% of native plants (Brosi et al, 2009) as well as some crops (Slaa et al, 2006). The morphology of the male reproductive tract has been described in some species of Meliponini (Cruz-Landim, 2001; Dallacqua & Cruz-Landim, 2003;Ferreira et al, 2004;Araújo et al, 2005;Lima et al, 2006;Lino-Neto et al, 2008;Brito et al, 2010;Ferreira et al, 2019). Although those studies have contributed in some extension to understand the reproduction Moure, 1950 (Meliponini, Apidae) During Sexual Maturation in these insects, they are restricted to few species and gaps about the reproductive biology and evolutionary history of stingless bees needs to be fills.…”
Section: Introductionmentioning
confidence: 99%
“…An intriguing finding in the male reproductive tract of stingless bees is the absence of accessory glands (Kerr, 1948;Ferreira et al, 2004Ferreira et al, , 2019. In insects, the accessory glands associated with the male reproductive tract produce compounds that are involved in functions such as spermatozoa maturation and activation, sperm and spermatophore formation, activation of oviposition in females, polygamy control including the formation of the mating plug (Chen, 1984;Gillot, 2003;Boosmam et al, 2005;Colonello & Hartfelder, 2005;Fuessl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations